Base genetica de los cultivares de arroz de riego liberados en Venezuela - Acevedo, M.=700 1 Torres, E.; Moreno, O.
(Es, En)
ilus., 14 ref.
Keywords: ARROZ ACUATICO; VARIEDADES; RIEGO; ORYZA SATIVA; REGISTRO; GENETICA; VENEZUELA; AGRONOMIA TROPICAL